2018
DOI: 10.5424/sjar/2018162-12076
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of farmer participation in direct marketing channels: A case study for cassava in the Oyo State of Nigeria

Abstract: Improving rural farmers’ access to direct agricultural markets is required to ensure sustainable supply of food. Rural farmers in the developing world account for the largest share of food supply including cassava. Globally, cassava (Manihot esculenta Crantz) is recognised as an important source of valuable semi-processed industrial raw materials such as ethanol, high-quality cassava flour and starch. However, there is less empirical research on rural farmers’ participation in direct marketing channels in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
3
19
0
3
Order By: Relevance
“…Various studies related to the market channel choice among smallholder farmers have classified the available market channels under different categories. Some consider it as a choice between informal and formal market channels (Kawala et al, 2018;Mafukata 2015), a direct or indirect sale to various intermediaries and users (Donkor et al 2018), while others have studied these channels through exploring the various value-chain actors and structures (Benmehaia 2019), or compared the institutional and technical factors involved (Panda & Sreekumar, 2012). Irrespective of the classification used, the choice of a market channel depends on a multitude of composite and inter-dependent factors, ranging from the economic, personal and social, to the technical, political and institutional.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Various studies related to the market channel choice among smallholder farmers have classified the available market channels under different categories. Some consider it as a choice between informal and formal market channels (Kawala et al, 2018;Mafukata 2015), a direct or indirect sale to various intermediaries and users (Donkor et al 2018), while others have studied these channels through exploring the various value-chain actors and structures (Benmehaia 2019), or compared the institutional and technical factors involved (Panda & Sreekumar, 2012). Irrespective of the classification used, the choice of a market channel depends on a multitude of composite and inter-dependent factors, ranging from the economic, personal and social, to the technical, political and institutional.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In addition, farmers with a large farm have higher bargaining power when dealing with processors than those with a smaller farm. Other empirical studies [11,54,55] also established a positive relationship between farm size and farmers' choice of marketing channel. Ownership of a motorbike encourages farmers to intensify their participation in the direct marketing channel.…”
Section: Discussionmentioning
confidence: 92%
“…The study's findings are consistent with those of existing studies [26,43,45] that found a positive relationship between farm output price and farmers' marketing channel choices (traders and wholesalers). On the contrary, Barrett [8] and Maspaitella, Garnevska [11] argued that price is not the only determinant of farmers' participation in a marketing channel, but non-price factors are equally important in affecting their marketing decisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations